Emerging Trends and Knowledge Domains of B2B Loyalty: A Scientometric Analysis - Seyed Javad Mohammadi; Abolghasem Ebrahimi; Shahrzad Tayaran; Sedighe Tootian Esfehani (‫مدیریت بازرگانی)
ObjectiveIn today's rapidly changing business environment, finding new customers is becoming increasingly difficult. As a result, companies are placing a strong emphasis on retaining their current customers. While there's a lot of research on customer loyalty in consumer-focused businesses (B2C), creating loyalty in business-to-business (B2B) settings is a unique challenge that needs a closer look. Therefore, the goal of this study is to understand how loyalty works in B2B companies and how it's evolving. MethodologyTo examine the advancements and developments within the domain of loyalty in B2B business models, articles on the Web of Science website were analyzed over 28 years (from 1994 to 2022) using scientometric methods and Sitespace software. FindingsResearch in the field of B2B loyalty has shown a growing trend. However, between 2011 and 2014, there was a decrease in research in this area. Subsequently, there has been an upward trend in research. Analysis of the top 10 countries in B2B loyalty indicates that the United States is now the leader in the number and breadth of loyalty research. Notably, countries like Taiwan and Spain are also actively engaged and flourishing in this field. A comprehensive review of B2B loyalty, encompassing its foundations, influential works, and intellectual connections between these works, revealed the key insights. The analysis unveiled highly cited articles, key authors, important keywords, intellectual milestones, and emerging research trends in the B2B loyalty domain. Overall, since 2014, B2B loyalty research has garnered increasing attention, with a significant rise in the number of articles published annually. The field has transitioned from a conceptualization stage to a cognitive psychology stage. Despite this growth, B2B loyalty research has not reached full maturity, necessitating further exploration of theoretical and methodological issues. New B2B loyalty research has introduced novel perspectives, such as attitudinal and behavioral angles, branding, service quality, and word-of-mouth communication. This diversification marks a new direction in B2B loyalty research. Additionally, the findings reveal that B2B researchers often use B2C theories as criteria for evaluating B2B loyalty. While B2B markets traditionally rely on high volume and cost-benefit analysis, loyalty in these markets also exhibits psychological aspects, indicating a new avenue for research. These results contribute to a deeper understanding of the boundaries of B2B loyalty research, providing valuable scientific information for researchers to guide the development of future studies. ConclusionThis research serves as a guide for future B2B loyalty studies, helping researchers identify directions and avoid duplicative efforts. Organizations can benefit from the concepts highlighted in this research, aligning their strategies to foster customer loyalty in the provision of products and services.